2015
DOI: 10.5588/ijtld.14.0811
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus is associated with cavities, smear grade, and multidrug-resistant tuberculosis in Georgia

Abstract: SUMMARY Setting National tuberculosis (TB) treatment facility, country of Georgia. Objective To determine the prevalence of diabetes mellitus (DM) and pre-DM among patients with TB using glycosylated-hemoglobin (HbA1c), and to estimate the association between DM and clinical characteristics and response to TB therapy. Design A cohort study was conducted (2011–2014) at the National Center for TB and Lung Disease in Tbilisi. Patients ≥35 years with pulmonary TB were included. HbA1c was used to define DM (≥6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 27 publications
6
53
3
2
Order By: Relevance
“…[11][12][13][14] Recent studies in Pakistan have shown more unfavourable outcomes among DS-TB patients with DM; 15,16 however, we could not find any relevant study examining the effect of DM on treatment outcomes among DR-TB patients in Pakistan.…”
contrasting
confidence: 48%
See 1 more Smart Citation
“…[11][12][13][14] Recent studies in Pakistan have shown more unfavourable outcomes among DS-TB patients with DM; 15,16 however, we could not find any relevant study examining the effect of DM on treatment outcomes among DR-TB patients in Pakistan.…”
contrasting
confidence: 48%
“…The lack of significant association observed between DM and DR-TB treatment outcome is consistent with findings from studies conducted in other countries, such as Georgia, Peru, Mexico and China. [11][12][13][14] However, studies in South Korea, Taiwan and Brazil have reported an association of DM with unfavourable outcomes. [7][8][9] These studies also report that unfavourable outcomes were significantly associated with poor glycaemic controls and other comorbidities caused by DM, such as chronic renal diseases, cardiovascular diseases and cerebrovascular diseases in patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Matthew J Magee et al shows that patients with TB and DM were more likely to have a higher AFB smear grade (aOR 2.37, 95% CI 1.14 -4.94). [11] Dooley, Kelly E et al shows higher sputum positivity in patients with DM. [12] Park SW et al shows a higher positive smear rates (p < 0.001) among diabetics as compared with nondiabetics.…”
Section: Proportion Of Dm Among Pulmonary Tuberculosis Patientsmentioning
confidence: 96%
“…It is known that TB occurs 3 times more often in patients with DM than in others [42,43]. The risk is greater if DM is not well controlled.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%
“…Thus some immunosuppression linked with DM is observed [44] and the delay in diagnosis is noted [45]. This is probably the cause of more advanced pulmonary disease presenting with cavities in newly recognised patients with tuberculosis and DM, comparing to those without DM [42,46]. DM is not only an important risk factor for tuberculosis but may also affect the disease course and treatment response.…”
Section: Diabetes Mellitus (Dm)mentioning
confidence: 99%